Integrasi Akuntansi Manajemen, Digitalisasi Qris Dan Prinsip Syariah Pengukuran Kinerja UMKM Menuju Ekonomi Berkelanjutan di Kecamatan Kabanjahe - Kamilah Kamilah; Muhammad Hafiz; Fazira Maharani; Elisa Fitri; Dewi Sundari; Irfan Muhdiya (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of QRIS-based MSME digitalization with sharia economics in realizing the principles of sustainable economic growth in Samura Village, Kabanjahe District, Karo Regency. The background of the study is based on low digital literacy, limited marketing access, and the dominance of cash transactions still carried out by local MSMEs. The research method uses a qualitative approach with observation techniques, interviews, and direct mentoring through the Real Work Lecture (KKN) program of the State Islamic University of North Sumatra. The results show that the implementation of QRIS can improve transaction efficiency, expand market reach, and increase consumer trust. In addition, the digital literacy program successfully encouraged MSMEs to utilize social media and use simple promotional media as a marketing tool. The integration of QRIS with sharia economic principles displays harmony with the values of justice, transparency, and benefit that are important foundations of sustainable development. Accounting theory is an important part of accounting practice. A proper understanding of this theory encourages the creation of sound and well-directed accounting practices. In the context of Sharia, accounting practices emerge as a solution to various problems found in conventional transactions that are not aligned with Islamic values. Thus, QRIS-based MSME digitalization can be used as a model in strengthening the local economy while supporting the achievement of the Sustainable Development Goals (SDGs).